دور الجمعيات الخيرية في التنمية الاجتماعية - جمعية دروب الخير بالوادي أنموذجا - شبرو، ليلى (University Of Eloued جامعة الوادي, 2024)
هدفت الدراسة إلى التعرف على دور جمعية دروب الخير في تحقيق التنمية الاجتماعية، جاء البحث لمعرفة هذا الدور من خلال اختيار عينة عشوائية من النشطاء والفاعلون بالجمعية لمعرفته، وذلك من خلال تصميم استمارة متعددة الأسئلة طُرحت على الفاعلين فيها، ومن ثَمَّ جرى جمع وتحليل البيانات واختبار الفرضيات باستخدام نموذج ألفا كرونباخ، وتوصل البحث إلى عدة نتائج أهمها أن جمعية دروب الخير تساهم في المجال الاجتماعي والصحي والثقافي بالإضافة للجانب الثقافي، وتوصل البحث لعدة نتائج أهمها اسهام جمعية دروب الخير في تحقيق التنمية المجتمعية من خلال النشاطات المختلفة التي تقوم بها. Research Summary: The study aimed to identify the role of the Paths of Charity Association in achieving social development. The research came to know this role by selecting a random sample of activists and actors in the association to know it, by designing a multi-question form that was asked to the actors in it, and then the data was collected and analyzed and hypotheses were tested. Using Cronbach's alpha model, the research reached several results, the most important of which is that the Paths of Charity Association contributes to the social, health, and cultural fields in addition to the cultural aspect. The research reached several results, the most important of which is the contribution of the Paths of Charity Association to achieving community development through the various activities it carries out.
مداخلة
Keywords: التنمية الاجتماعية; الجمعيات الخيرية; جمعية دروب الخير; charitable societies; social development; Paths of Charity Association